Effect of physical factors on hydrolytic enzyme action of seed bone Alternaria Species - Rathod, Sulochana R; Chavan, Ashok M (Current Botany, 2012)
Impact of physical factors on hydrolytic enzyme production of Alternaria species was studied. Continuous light favored enzyme production in Alternaria species. Maximum enzyme activity occurred in 15 – 20 days in all the Alternaria species. Alternaria species produced hydrolytic enzymes maximum at 20 – 30oC temperature.All the species of Alternaria at 5.5 to 6.5 pH value produced maximum enzyme, however pH 3.5 and 8.5 inhibited enzyme activity.